Answer:
y = -2x+2
Step-by-step explanation:
First we find the slope
m = (y2-y1)/(x2-x1)
= (-2-4)/(2--1)
= (-2-4)/(2+1)
-6/3
-2
We have the slope =-2
We can substitute it into the equation
y = mx+b where m is the slope and b is the y intercept
y =-2x+b
Use a point for x and y to solve for b
4 = -2(-1) +b
4 = 2+b
Subtract 2 from each side
4 -2 = -2+2+b
2 = b
We know m and b
y = -2x+2
Answer:
y = -2x + 2
Step-by-step explanation:
Slope: (-2-4)/(2--1) = -6/3 = -2
y - 4 = -2(x - -1)
y = -2x - 2 + 4
y = -2x + 2